Galerie - Stalmans, Jan (Antwerpen : MIM, Ortelius Reeks, 1986)
Mara, Pol ; Van Hoeydonck, Paul ; Landuyt, Octave ; Vermeersch, Jose ; Vandenbranden, Guy ; Vanriet, Jan ; Minnebo, Hubert ; Dries, Jan ; Van Tuerenhout, Jef ; Poot, Rik ; Silvain, Christian ; Delvaux, Paul
boek